The cost-effectiveness and cost-utility of at-home infrared temperature monitoring in reducing the incidence of foot ulcer recurrence in patients with diabetes (DIATEMP): study protocol for a randomized controlled trial - Wouter B. aan de Stegge; Nora Mejaiti; Jaap J. van Netten; Marcel G. W. Dijkgraaf; Jeff G. van Baal; Tessa E. Busch-Westbroek; Sicco A. Bus (Trials, 2018)
Abstract Background Home monitoring of foot temperatures in high-risk diabetes patients proves to be a promising approach for early recognition and treatment of pre-signs of ulceration, and thereby ulcer prevention. Despite previous studies demonstrating its efficacy, it is currently not widely applied in (Dutch) health care. Methods In a multicenter, outcome-assessor-blinded, randomized controlled trial, 304 patients with diabetes mellitus types I or II, loss of protective sensation based on peripheral neuropathy, and a history of foot ulceration in the preceding 4 years or a diagnosis of Charcot neuro-osteoarthropathy will be included. Enhanced therapy will consist of usual care and additional at-home daily measurement of foot temperatures at six to eight predefined locations on the foot. If a contralateral foot temperature difference of > 2.2 °C is found on two consecutive days, the participant is instructed to contact their podiatrist for further foot diagnosis or treatment, and to reduce ambulatory activity by 50% until temperatures are normalized. Enhanced therapy will be compared to usual care. The primary outcomes are the cost (savings) per patient without a foot ulcer (i.e., cost-effectiveness) and per quality-adjusted life year gained (i.e., cost-utility). The primary clinical outcome in the study is the proportion of patients with foot ulcer recurrence on the plantar foot, apical surfaces of the toes, the interdigital spaces or medial and lateral forefoot surfaces during 18-month follow-up. Discussion Confirmation of the efficacy of at-home foot temperature monitoring in ulcer prevention, together with assessing its usability, cost-effectiveness and cost-utility, could lead to implementation in Dutch health care, and in many settings across the world. Trial registration Netherlands Trial Registration: NTR5403. Registered on 8 September 2015.